Intermediate phase assisted sequential deposition of reverse‐graded quasi‐2D alternating cation perovskites for MA‐free perovskite solar cells. Issue 3 (1st February 2023) - Wang, Shaofu; Liu, Yumin; Zou, Junjie; Jin, Junjun; Jiang, Yun; Zeng, Tao; Zhao, Wenyan; He, Rong‐Xiang; Chen, Bolei; Chen, Yu; Jin, Shuoxue; Li, Hong‐Xiang; et al.
Abstract: One‐step deposition approaches have been widely applied and developed in the fabrication of quasi‐2D perovskites. However, the regulation of quantum wells (QWs) and crystalline orientation is difficult and complicated when using this methodology. Sequential deposition is another widespread synthetic approach for preparing perovskite films and perovskite dimension engineering. In this article, δ ‐CsPbI3 intermediate phase assisted sequential (IPAS) deposition is successfully carried out to fabricate MA‐free quasi‐2D ACI perovskites. The amount of the δ ‐CsPbI3 intermediate phase in the PbI2 layer and the concentration of GAI molecule in the IPA solution both play important roles in the production of MA‐free quasi‐2D ACI perovskite films. The n value of the MA‐free quasi‐2D ACI perovskites can be adjusted, which affects the photovoltaic performance and device stability. Compared with one‐step deposition, the MA‐free quasi‐2D ACI perovskites prepared via IPAS deposition have opposite reverse‐graded QW distribution and improved vertical orientation, leading to a remarkable PEC of up to 18.86% and allowing the preparation of unpackaged devices with prominent working stability (80%, 400 h). The underlying mechanism and crystallization pathway of IPAS deposition confirm that sequential deposition has unique superiority in regulating the QW distribution and crystalline orientation of quasi‐2D perovskites. Abstract : The δ ‐CsPbI3 intermediate phase assisted sequential (IPAS) deposition is successfully carried out to prepare MA‐free quasi‐2D ACI perovskite films. The amount of the δ ‐CsPbI3 intermediate phase in the PbI2 layer is the key to the formation of quasi‐2D ACI perovskites. Compared with the more popular one‐step deposition, the intrinsic reverse‐graded QW distribution and highly vertical orientation achieved by IPAS deposition mean that this approach is highly superior for fabricating quasi‐2D perovskites.